Designing User Experience Design of the Healthy Diet Mobile Application Using the Fives Planes Framework - Agusdin, Riza Prapascatama; Salsabila, Amira; Kartika Putri, Dyah Anggraini (Jurnal Buana Informatika, 2021)
Abstract. Obesity and overweight are becoming increasingly common conditions. On the other hand, the rapid development of technology shows by the increasing number of smartphone users. M-health application can be a solution to the burden of existing health problems. In line with that, the research focused on the quality improvement of user experience in m-Health, especially diet-related apps widely conducted. This study aims to design user experience in a diet-support mobile application called Health-Key using the five planes framework by evaluating usability aspects using the User Acceptance Test. The result of this study is prototype design. Evaluation shows that the designed prototype has good interface, practicality, and efficiency indicator, and 76.9% of respondents stated that the application is feasible, appropriate, useful, and it potentially developed in further iteration with improvements according to the respondents' suggestions.Keywords: m-health, healthy diet, user experience, five planes framework, user acceptance test.Â Abstrak. Designing User Experience Design of The Healthy Diet Mobile Application Using The Fives Planes Framework. Obesitas dan kelebihan berat badan menjadi kondisi gangguan kesehatan yang umum dialami. Di sisi lain, perkembangan teknologi yang kian pesat ditunjukkan dengan semakin banyaknya pengguna smartphone. Aplikasi M-Health (Mobile Health) dapat menjadi solusi dari beban permasalahan kesehatan yang ada. Sejalan dengan itu, penelitian yang berfokus pada peningkatan kualitas pengalaman pengguna M-Health, khususnya aplikasi pendukung diet, banyak dilakukan. Penelitian ini bertujuan untuk merancang desain pengalaman pengguna dalam aplikasi mobile yang mendukung pola diet sehat bernama Health-Key menggunakan The Fine Planes Framework serta mengkombinasikannya denga mengevaluasi aspek kegunaan dengan User Acceptance Test. Hasil dari penelitian ini adalah desain prototipe. Evaluasi menunjukkan bahwa prototipe yang dirancang memiliki indikator antarmuka, kepraktisan, dan efisiensi yang baik, serta 76,9% responden menyatakan bahwa aplikasi layak, tepat-guna, bermanfaat, dan berpotensi dikembangkan dalam iterasi perancangan lebih lanjut dengan perbaikan sesuai saran responden.Kata Kunci: m-health, healthy diet, user experience, five planes framework, user acceptance test.